The Indonesia Report: National Landscape, Current Challenges and Opportunities for Growth - Institute for Societal Leadership (Institutional Knowledge at Singapore Management University, 2015)
A maritime analogue to the silk road running through Central Asia, the Indonesian archipelago was a key ancient trade route linking Chinese goods to markets in India and farther west into the Mediterranean. Its cosmopolitan ports attracted signiﬁcant numbers of Arab, Indian and Chinese merchants and holy men and fostered the exchange of goods as well as cultural and religious ideas. Cultural appropriation had a clear Indian bias. Starting in the early eighth century, the various islands saw the rise and fall of several Indianised Buddhist and Hindu kingdoms, including Mataram, Singhasari and Majapahit in east Java and Srivijaya in Sumatra. Islam, which now forms the majority religion of modern Indonesia, also came with Indian merchants from Gujarat and the Coromandel Coast. Several mainstays of Indonesian culture, such as its religious architecture, traditional dances and use of Indian epics in the wayang, belie strong Indic inﬂuences.